Chromatographic Separation of Preconcentrated Vitamin E from Palm Fatty Acid Distillate - Chu, Boon Seang (2004)
The importance of vitamin E as a lipid-soluble antioxidant that protects unsaturated fatty acids against oxidative deterioration is widely known. An important source of vitamin E is the fatty acid distillate from deodorization during the refining of vegetable oils. The purpose of this study was to develop a method for separating vitamin E from palm fatty acid distillate (PFAD) obtained from palm oil refining. Vitamin E in PFAD was first concentrated by enzymatic hydrolysis. The free fatty acids liberated by the hydrolysis, together with those already present in PFAD, were neutralized by sodium hydroxide. A vitamin E-rich fraction was then extracted from the hydrolyzed and neutralized PFAD using hexane. The fraction obtained was finally subjected to normal phase adsorption chromatography with packed silica gel. Two elutions were done in the chromatography: the vitamin E in hexane was adsorbed on silica gel and the extraneous matter eluted out in the first elution, while the second elution released the vitamin E from the silica gel.Reaction variables such as temperature, lipase concentration and water content in the reaction mixture affected the enzymatic hydrolysis of PFAD. Regression models generated from Response Surface Methodology adequately explained the data variation and significantly represented the actual relationships between the reaction parameters and responses. It was suggested from this study that for the maximum vitamin E concentration, the hydrolysis should be carried out with 2.5% w/w lipase and 45.2−47.3% v/w water for 5.5−5.7 h. Screening tests concluded that silica gel was suitable for adsorption of vitamin E. Batch mode adsorption and desorption experiments were employed to study the equilibrium and kinetics of the adsorption and desorption processes. Vitamin E uptake by silica gel was rapid with adsorption equilibrium achieved in about 5 min. The adsorption isothermic data were in good agreement with the Langmuir model, suggesting that the vitamin E adsorbed on silica gel was monolayer. Kinetics study of batch adsorption revealed that the rate of vitamin E uptake by silica gel followed a pseudo-second order reaction and involved both external mass transfer and intraparticle diffusion. Intraparticle diffusion was the rate-limiting step during the adsorption as it needed a higher magnitude of activation energy (–25.45 and –54.13 kJ mol-1 for external mass transfer and intraparticle diffusion, respectively). The adsorption of vitamin E on silica gel was exothermic, while the reverse was true for desorption. Desorption exhibited a bi-phasic characteristic with an initial fast release of the vitamin followed by a much slower phase. The two distinct rates were probably due to heterogeneities in the adsorbing surfaces. Since the silica gel surface is composed of both high-energy silanol groups and low-energy siloxane groups, it was postulated that the releases of vitamin E molecules from these two groups were responsible for the slow and rapid desorption processes, respectively. Entrapment of the vitamin E molecules in the micropores of the silica gel may also have contributed to the slow desorption in the second phase. The desorption isotherm could be fitted in the Freundlich model. Adsorption of vitamin E on silica gel was also tested in a fixed-bed column. The breakthrough curve of vitamin E adsorption in the column showed a typical S-shaped profile. The service time of the column increased with the column bed height, but decreased with increasing inlet vitamin E concentration, column temperature and flow rate. The column efficiency in terms of adsorbent usage rate could be improved by decreasing the inlet vitamin concentration and flow rate. Since adsorbing vitamin E on silica gel was exothermic, increasing the column temperature decreased the column capacity. The desorption of vitamin E in a column system reflected the “two-distinct-rate” desorption behavior found in batch desorption systems. This slow desorption was the rate-controlling step in the recovery of vitamin E. The desorption rate increased with column temperature but decreased with column bed height and flow rate. The recovery of vitamin E was high for all systems - 94.8 to 98.8% - with a vitamin E concentration in the extract of 18.5−21.5%. The results from this work demonstrate the potential applicability of the current separation method for recovering vitamin E from PFAD. Detailed descriptions of the enzymatic hydrolysis and adsorption/desorption of vitamin E in adsorption chromatography have provided useful information for a better understanding of the current separation process. The method described offers an alternative to the existing vitamin E separation methods. It can be applied as one of a series of steps in producing a high-purity vitamin E concentrate from PFAD.